2019
DOI: 10.1039/c9ra06251c
|View full text |Cite
|
Sign up to set email alerts
|

To beat the heat – engineering of the most thermostable pyruvate decarboxylase to date

Abstract: Pyruvate decarboxylase (PDC) is a key enzyme for the production of ethanol at high temperatures and for cell-free butanol synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
2
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
2
2
2
Order By: Relevance
“…Surprisingly, DHADs from Cupriavidus ( Cn H16-, Cn N1-, and Cm DHAD), although having relatively high activities toward d -glycerate and high T m values, exhibited relatively modest TTNs (∼20000). This result is in contrast to our previous studies with α-keto acid decarboxylases, in which we observed a direct relationship between T m and kinetic stability. , The melting temperature ( T m ) may indicate the general stability (thermodynamic stability) of an enzyme . Thus, in the case of proteins with similar initial activities and T m values, a lower TTN could be linked to rapid loss of activity over time rather than to thermal denaturation.…”
Section: Resultscontrasting
confidence: 99%
“…Surprisingly, DHADs from Cupriavidus ( Cn H16-, Cn N1-, and Cm DHAD), although having relatively high activities toward d -glycerate and high T m values, exhibited relatively modest TTNs (∼20000). This result is in contrast to our previous studies with α-keto acid decarboxylases, in which we observed a direct relationship between T m and kinetic stability. , The melting temperature ( T m ) may indicate the general stability (thermodynamic stability) of an enzyme . Thus, in the case of proteins with similar initial activities and T m values, a lower TTN could be linked to rapid loss of activity over time rather than to thermal denaturation.…”
Section: Resultscontrasting
confidence: 99%
“…No significant difference was observed when comparing the thermodynamic stability of Cn L-KdpD and Hs L-KdpD, although the kinetic stability suggested otherwise. Apparently, the relationships between the kinetic and thermodynamic stabilities were not able to be observed for L-KdpD, which stands in contrast to our previous studies of two α-keto acid decarboxylases (Sutiono et al 2018 ; Sutiono et al 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
“…One current example is the development of minimized biocatalytic reaction cascades in cell‐free processes for the conversion of glucose to ethanol or isobutanol using only six or eight enzymes, respectively. Enzymes required for such routes are being developed to work at elevated temperatures [32] . The production of alcohols working at high temperatures can be useful to enable easy removal of the volatile product and reduce the risk of contamination.…”
Section: Resultsmentioning
confidence: 99%